Spatial Analysis of Land Use and Land Utilization Based on Suitability Spatial Planning on Food Estate Planning Site in Kapuas Regency, Central Kalimantan - Budianto, Budianto; Susiloningtyas, Dewi; Dimyati, Muhammad (Indonesian Journal of Earth Sciences, 2024)
The limited space on land increases the importance of spatial planning that is transparent, accountable, and effective, which involves multi-stakeholders in its conception. Such planning is intended to create a spatial arrangement that supports security, productivity, and sustainability. In an attempt to secure food supply in the future, the government of Indonesia initiated a Food Estate program in 2020. This study analyzes land use and land utilization in regions planned for a food estate project in Kapuas Regency, Central Kalimantan, and evaluates their suitability with the designated spatial planning. The method used land surveying and spatial analysis to answer the research objective. The result explained that 85,492.58 Ha (49.20%) of land use is suitable for spatial planning. The area of 88,786.43 Ha (51.09%) of land utilization is suitable for its spatial planning. The survey was carried out at the early stage of spatial planning implementation throughout spatial development is ongoing. Development results that are in accordance with the spatial planning have not yet been seen, this happens because the determination of the spatial planning and the spatial suitability analysis are too close together. The food estate program has not been included in the Kapuas Regency spatial planning. The results of the research concluded that there was a large mismatch gap, it was necessary to revise the spatial planning by including the food estate program in the regional spatial planning.